The foundational layouts of Rome - Boudon, Pierre (Estudos Semióticos, 2023)
Following the collective work published by Marcel Detienne (1990), we have taken up again the theme of foundational layouts, in particular that of ancient Rome, inaugurated by Romulus according to a foundation ritual (Plutarch). It is for us the occasion to take again our analysis of the places and to develop them from a thematization according to our semiotic approach by means of a logico-topological schematization called templum. It is through the notion of mythogram that we have differentiated this approach: structure of orientation of a space, actantiality associated with types of ritual, planning of an urban order that will be found throughout Roman history. These three correlated schematizations – to which it would be necessary to associate, in an underlying way, the logic of establishment of the place developed in our precedent book (2013) – make it possible to characterize the idea of a typical « urban form » in its recurrence.